Thyroid dysfunction and sarcopenia: a two-sample Mendelian randomization study - Wei, Jiaxin; Hou, Shuanglong; Hei, Peng; Wang, Gang (Frontiers in Endocrinology, 2024)
Objective Observational studies have shown positive associations between thyroid dysfunction and risk of sarcopenia. However, the causality of this association remains unknown. This study aimed to evaluate the potential causal relationship between thyroid dysfunction and sarcopenia using Mendelian randomization (MR). Methods This study collected pooled data from genome-wide association studies focusing on thyroid dysfunction and three sarcopenia-related features: low hand grip strength, appendicular lean mass (ALM), and walking pace, all in individuals of European ancestry. The primary analytical method used was inverse-variance weighted, with weighted median and MR-Egger serving as complementary methods to assess causal effects. Heterogeneity and pleiotropy tests were also performed, and the stability of the results was evaluated using the Leave-one-out. Results The MR analysis indicated that hyperthyroidism could lead to a significant decrease in ALM in the extremities (OR = 1.03; 95% CI = 1.02 to 1.05; P < 0.001). The analysis also found that hypothyroidism could cause a notable reduction in grip strength (OR = 2.03; 95% CI = 1.37 to 3.01; P < 0.001) and walking pace (OR = 0.83; 95% CI = 0.77 to 0.90; P < 0.001). There was a significant association between subclinical hyperthyroidism and a reduced walking pace (OR = 1.00; 95% CI = 0.99 to 1.00; P = 0.041). Conclusion This study provides evidence that hyperthyroidism, hypothyroidism, and subclinical hyperthyroidism can all increase the risk of sarcopenia.